Spatio-temporal correlation between growth of science and technology innovation parks (STIPs) and urban development in Yangtze Delta region (YDR), China using remote sensing and GIS techniques - Yue Wu; Siyuan Zhang; Auwalu Faisal Koko; Zexu Han (Geocarto International)
Science and Technology Innovation Parks (STIPs) are critical urban and economic development drivers, particularly in regions experiencing rapid industrialization. This study investigates the spatio-temporal trends and relationships between the growth of STIPs and urban development indicators in China’s Yangtze Delta Region (YDR). Using a mixed-method approach that integrates regression analysis with geospatial techniques, the research analyzes key metrics such as Gross Domestic Product (GDP), industrial structure, innovation capacity, population growth, and land utilization. The findings reveal a strong positive correlation, where an average 1% increase in STIPs contributes to a 0.7015% rise in GDP. Land use indicators, particularly built-up area expansion, exhibited a strong interdependence with STIP proliferation. These results underscore the strategic importance of STIPs in enhancing economic vitality and sustainable urban planning. The study offers valuable insights for policymakers and urban planners in the YDR and other rapidly urbanizing regions, emphasizing integrating technology-driven development into urban management strategies.